On-chip arbitrary-mode spot size conversion - Qi Wei; Yu Yu; Zhang Xinliang (Nanophotonics, 2020)
Manipulating on-chip optical modes via components in analogy with free-space devices provides intuitional light control, and this concept has been adopted to implement single-lens–assisted spot size conversion using integrated device. However, the reported schemes have been demonstrated only for fundamental mode, while high-order or irregular modes are preferred in specific applications. The 4-f system is widely used in Fourier optics for optical information processing. Under the inspiration of the 4-f system and the beam expander in bulk optics, a spot size converter (SSC) with two metamaterial-based graded-index waveguides is proposed and demonstrated. The proposed device is capable of widening an arbitrary mode while preserving its profile shape. Compared with conventional SSC using adiabatic taper, the footprint can be reduced by 91.5% under a same intermode crosstalk. Experimentally, an expansion ratio of five is demonstrated for regular modes. Furthermore, for an irregular mode, the functionality is numerically verified without structure modification. This work offers a universal solution to on-chip spot size conversion and may broaden the on-chip application prospects of Fourier optics.